PENGARUH SISTEM INFORMASI AKUNTANSI DAN PELATIHAN KERJA TERHADAP KINERJA KARYAWAN PT. BANK MANDIRI (PERSERO) Tbk AREA PLUIT SELATAN - Eka Kusuma Dewi; Anggun Putri Romadhina (JURNAL AKUNTANSI BARELANG, 2022)
This study aims to analyze the accounting information system and job training on employee performance either partially or simultaneously. This research was conducted at Pt Bank Mandiri (Persero) Tbk South Pluit Area. The type in this research is quantitative research. This sampling uses a saturated sample technique in which all the population is sampled in this study, amounting to 57 respondents, and data collection in this study includes observation, questionnaires and literature study. Data analysis techniques in this study are validity, reliability, classical assumption test, descriptive analysis, multiple linear analysis and hypothesis testing. by using the SPSS Version 25 application program. The results of this study indicate that simultaneously accounting information systems and job training affect employee performance, partially accounting information system affects employee performance and job training affects employee performance.